ANALISIS KELAYAKAN FINANSIAL PADA USAHA PENGGEMUKAN SAPI (Bos taurus) DI KABUPATEN OKU TIMUR - aisyah aisyah (JASEP, 2023)
The development of livestock in South Sumatra Province aims to increase the income and welfare of breeders, fulfill the consumption of food originating from livestock, industrial and export raw materials, provide employment opportunities, increase the institutional role of breeders and achieve a balance between utilization and preservation but more on efforts to increase the income and welfare of breeders. local. The East OKU Regency Government will partner with banks as working capital providers in a cattle fattening program involving a number of cattle breeders. The cattle fattening program is expected to be able to improve the welfare of the community, especially cattle breeders, to know how to do business with the hope that when the price of rubber sap decreases as it is today, the community can take another alternative, namely fattening cattle. The problems faced are how much income the cattle fattening business generates and whether the cattle fattening business in East OKU Regency is feasible to be developed financially. The purpose of this study was to analyze the income and financial feasibility of fattening cattle in East OKU District. The conclusion is that the development of the cattle fattening business needs to be continuously pursued because it has good prospects, through cooperation between the government/private sector and farmer groups or breeders (cooperatives). Breeders who will be partners should be selected based on their characteristics and made forage gardens to ensure continuous availability of feed.Keywords : Cattle fattening business, income, feasibility